2011
DOI: 10.1097/ico.0b013e3181eeb44a
|View full text |Cite
|
Sign up to set email alerts
|

Deep Anterior Lamellar Keratoplasty Using Big-Bubble Technique for Treatment of Corneal Stromal Scars

Abstract: DALK big-bubble technique may be a valuable and safe treatment in patients with corneal stromal scar with healthy endothelium. The visual and refractive outcomes are comparable to standard penetrating keratoplasty, avoiding the risk of endothelial rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…It was determined that allograft rejection episodes after DALK were fewer and milder compared to those after PK [24]. Endothelial rejection can be largely reduced by retaining endothelium during the DALK procedure [25]. In our series, the allograft rejection rate after DALK was 2.3% (one eye), which was significantly lower than that after PK (28.4%, 21 of 74 eyes), in the treatment of HSK at our institution [17].…”
Section: Discussionmentioning
confidence: 74%
“…It was determined that allograft rejection episodes after DALK were fewer and milder compared to those after PK [24]. Endothelial rejection can be largely reduced by retaining endothelium during the DALK procedure [25]. In our series, the allograft rejection rate after DALK was 2.3% (one eye), which was significantly lower than that after PK (28.4%, 21 of 74 eyes), in the treatment of HSK at our institution [17].…”
Section: Discussionmentioning
confidence: 74%
“…The mean endothelial cell count 6 to 12 months after surgery was 2458 6 330 cells per square millimeter. 15 Another report demonstrated that the endothelial cell count 6 and 12 months after DALK was 1908 6 516 cells per square millimeter and 1835 6 491 cells per square millimeter, respectively. 25 Our results showed that the endothelial cell count after a mean follow-up of 50 months was 1738 6 573 cells per square millimeter, even when the preoperative corneal scars reached near the level of DM.…”
Section: Discussionmentioning
confidence: 97%
“…[14][15][16] In addition to the obvious advantage of absence of endothelial graft rejection, DALK allows the use of poor-quality donor corneas thereby alleviating the problem of shortage of donor corneas in the developing world. 20,21 Considering these factors, we performed DALK for patients with deep HSKinduced corneal scars with functional endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The development of DALK techniques and the improved quality of the donor button preparation have resulted in significantly better visual acuity outcomes. 15,16,20,62,[85][86][87][88] …”
Section: A Visual Acuitymentioning
confidence: 99%